2006
DOI: 10.1007/s11373-006-9087-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-20: biological functions and clinical implications

Abstract: SummaryIL-20 belongs to the IL-10 family and plays a role in skin inflammation and the development of hematopoietic cells. Little is known about its other biological functions and clinical implications, however.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 69 publications
0
38
0
Order By: Relevance
“…Accumulating evidence has revealed the association of IL-19, [8][9][10][11][12] IL-20 [13][14][15][16][17][18][19][20] and IL-24 [21][22][23][24][25][26] with diseases. To explore if any soluble receptors of these cytokines could function as antagonists of the cytokines, we tried to isolate the alternative spliced transcripts of the receptors for IL-19, IL-20 and IL-24.…”
Section: Isolation Of Mil-20r1 Splice Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has revealed the association of IL-19, [8][9][10][11][12] IL-20 [13][14][15][16][17][18][19][20] and IL-24 [21][22][23][24][25][26] with diseases. To explore if any soluble receptors of these cytokines could function as antagonists of the cytokines, we tried to isolate the alternative spliced transcripts of the receptors for IL-19, IL-20 and IL-24.…”
Section: Isolation Of Mil-20r1 Splice Variantmentioning
confidence: 99%
“…In response to ligand binding, the CRF2 proteins form heterodimers, leading to cytokine-specific cellular responses. The biological effects of these three cytokines appear quite distinct: immune activity with IL-19, [7][8][9][10][11][12] skin biology, atherosclerosis and synovial biology in rheumatoid arthritis with IL-20, [13][14][15][16][17][18][19][20] and tumor apoptosis with IL-24. [21][22][23][24][25][26] Within the CRF2 family, only IL-22 binding protein was identified as a decoy receptor functioning as a naturally occurring, highly specific IL-22 antagonist in both humans [27][28][29] and mice.…”
Section: Introductionmentioning
confidence: 99%
“…rIL-20 and rIL-24 might promote angiogenesis (12,13). IL-19 was reported to up-regulate Th2 cytokines in an animal model of asthma (14).…”
mentioning
confidence: 99%
“…It was also reported that IL-20 induced IL-6 and TNFin monocytes, stimulated the expression of keratinocytes growth factor (KGF), IL-6, TNFand reactive oxygen species (ROS) in CD8+ T cells (Wei et al, 2006). In psoriasis, the two most important effects of IL-20 are the inhibition of normal terminal differentiation of keratinocytes and the induction of anti-bacterial proteins (Wolk et al, 2009a).…”
Section: Keratinocytes and Il-20mentioning
confidence: 99%